Response of juvenile pacu (Piaractus mesopotamicus Holmberg, 1887) to balanced digestible protein - Khan, Kifayat Ullah [UNESP]; Gous, Robert Mervyn; Mansano, Cleber Fernando M.; Nascimento, Thiago Matias T. [UNESP]; Romaneli, Rafael de S. [UNESP]; Rodrigues, Andressa Tellechea [UNESP]; Sakomura, Nilva Kazue [UNESP]; Fernandes, João Batista K. [UNESP] (Hindawi, 2020)
This 45-day work aimed to determine the response of juvenile pacu (Piaractus mesopotamicus) to balanced digestible protein (BDP) and to use these responses to determine whether the optimum economic levels of BDP would differ depending on the form in which the fish is sold. Six isoenergetic diets containing 163, 201, 238, 272, 315 and 348 g/kg BDP (dry-matter basis) were prepared through the serial dilutions of a high-protein diet with the low-protein diet. Fish (initial average body weight, 10.82 ± 0.14 g) were fed with respective experimental diets three times a day until apparent satiation. The optimum biological level of BDP was calculated as 326 g/kg (dry-matter basis) by the quadratic regression model for maximum body weight gain of juvenile pacu. To maximize economic returns (US$/kg) for different end products, the optimum economic levels of BDP were calculated as 311, 317 and 319 g/kg (dry-matter basis) by an economic model for whole-body, eviscerated and sliced juvenile pacu respectively. This finding revealed that obtaining maximum biological performance of fish in the case of high feed costs or low prices of the end product in consumer market would substantially reduce the economic returns.
Keywords: amino acid balance; biological and economic performance; dietary protein; modelling in nutrition; Piaractus mesopotamicus